Mapping Regional Economic Resilience: Analysis of Volatility and GRDP Recovery of Poverty Reduction in Indonesia - Sutrisno Sutrisno; Hardian Mursito; Muhammad Nur El Farabi; Anna Nurfarkhana (Jurnal Pemberdayaan Masyarakat, 2025)
Regional economic resilience in the face of internal and external economic shocks plays a central role in shaping the standard of living for a community and creating sustainable regional development. The purpose of this study is to map regional economic resilience by analyzing GRDP volatility, the level of post-pandemic economic recovery, and the relationship between economic growth and poverty indicators. Using a quantitative and descriptive-analytical approach, the analysis of economic volatility, recovery rates, and growth rates produced the following findings: (1) Economic resilience varies across Indonesia. Provinces with diversified economies show lower volatility, while regions that rely on extractive sectors tend to have high volatility; (2) The use of both constant and current price bases for GRDP calculations, bases ADHK and ADHB, showed similar growth trends at the macro level. However, these different methods yielded significant variations in detail, offering distinct perspectives on each region's economic performance. (3) Structural and methodological factors influence the results, which are then used to assess the strength of each economic sector. By understanding these methodological differences and the dynamics of growth, volatility, and recovery, policymakers can formulate targeted intervention strategies to support integrated community welfare and optimize resource allocation, thereby promoting economic stability and growth.